2021
DOI: 10.35808/ersj/2390
|View full text |Cite
|
Sign up to set email alerts
|

Does Adoption of Latest Modifications of IAS 16 Influence on Company’s Profitability? Evidence from European Companies

Abstract: Purpose: This study aims to investigate the influence of applying IFRS on European companies' profitability. The research focuses on adopting the new IFRS 16, specifically the accounting treatment of leases. The new standard introduces revolutionary changes in the treatment of leasing contracts. Many companies have moved away from IFRS, so it is essential to check the impact of IFRS on other companies. Design/Methodology/Approach: The study includes an analysis of two periods, before and after implementing IFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Although there are studies on the effects of CPC 06 (R2) on balance sheet and on SPL Companies' (e.g. Campanha & Santos, 2020;Luty & Petković, 2021;Messias et al, 2022;, until the date of the present article, no studies have been found to discuss these effects on VAS. Thus, to fill this gap, the present article was elaborated whose objective was to analyze the effects of the adoption of CPC 06 (R2) on the rent line of the VAS and in the percentage of value-added distributed as rents.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Although there are studies on the effects of CPC 06 (R2) on balance sheet and on SPL Companies' (e.g. Campanha & Santos, 2020;Luty & Petković, 2021;Messias et al, 2022;, until the date of the present article, no studies have been found to discuss these effects on VAS. Thus, to fill this gap, the present article was elaborated whose objective was to analyze the effects of the adoption of CPC 06 (R2) on the rent line of the VAS and in the percentage of value-added distributed as rents.…”
Section: Introductionmentioning
confidence: 87%
“…Using a sample composed of financial statements from 2017 to 2019 of 996 companies, Luty and Petković (2021) tested the hypothesis that IFRS 16 has significantly impacted the profitability of European companies. It was confirmed that there was an improvement in the profitability of companies after the adoption of the standard.…”
Section: Accounting Treatment Of Leases and Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common cosmetic accounting occurs when determining the accounting treatment of depreciation (IAS 16) [34], revenue recognition (IFRS 15), the disposal of intangible assets (IAS 38) or fair value measurement (IFRS 13). The influence of applying IAS 16 on an entity's financial reporting was proven both theoretically and practically by [35], as the results of the revaluation of non-current assets to fair value may lead to a certain level of subjectivity in the determination of this value, but the impacts on the company's financial position, as well as its performance, are direct [36]. Additionally within the context of IAS 16, there is the alternative of changing depreciation regimes for fixed assets, a method that is decided by company management but that can significantly influence stakeholder decisions [37].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Apesar de existirem trabalhos sobre os efeitos do CPC 06 (R2) no balanço patrimonial e na DRE das empresas (e.g. Campanha & Santos, 2020;Luty & Petković, 2021;Messias et al, 2022;, até a data do presente artigo, não se encontraram pesquisas voltadas a debater tais efeitos na DVA. Assim, buscando preencher esta lacuna, elaborou-se o presente artigo cujo objetivo foi analisar os efeitos da adoção do CPC 06 (R2) na rubrica de aluguéis da DVA e no percentual de distribuição do valor adicionado como aluguéis.…”
Section: Introductionunclassified